HUBUNGAN ANTARA PENDIDIKAN, PENGETAHUAN DAN PRAKTIK HYGIENE SANITASI PENJAMAH MAKANAN TERHADAP KEBERADAAN BAKTERI STAPHYLOCOCCUS AUREUS PADA HIDANGAN HEWANI DI SALAH SATU CATERING KOTA SEMARANG - Vivit Nilasari; Yuwono Setiadi; Dyah Nur Subandriani; Meirina Dwi Larasati; Arintina Rahayuni (Poltekkes Kemenkes Semarang, 2019)
Background: the Staphylococcus aureus bacteria is one of the microbes that can causes gastroenteritis. This bacterium normaly was live as a human. The role of food handlers is very important in the existence of the Staphylococcus aureus bacteria.Objective: to find out the relationship between education, knowledge and hygiene practice of food handler’s sanitation toward the existence of the Staphylococcus aureus bacteria on animal dishes at Shella’s Catering Semarang.Methods: this study used descriptive analytic with cross sectional design, the number of samples is 9 samples of animal dishes with 2 times repetition. Staphylococcus aureus can be identified by conductingan the MSA test. The data of education, knowledge and practice of food handler’s hygiene sanitation were collected using questionnaires through interview. The statistical test used Fisher's exact.Results: the knowledge and practice of food handler’s hygiene sanitation were categorized good (60%). The results of the bivariate test showed that there was no correlation between education, knowledge and practices of hygiene sanitation on the existence of the Staphylococcus aureus bacteria in animal dishes (p 0.05)Conclusion: there is no relationship between education, knowledge and hygiene practice of food handler’s sanitation toward the existence of the Staphylococcus aureus bacteria in animal dishes.